Tradisi Nikah Massal Para Santri di Pondok Pesantren Darul Falah Pusat: Pendekatan Maslahah Mursalah As-Syathiby - Muhammad Kharis Akhsan Rifqy; Siti Masrohatin; Mokhammad Miftahul Huda; Muhammad Faisol (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The mass wedding of students that has been carried out repeatedly at the Darul Falah Central Islamic Boarding School has become an existing tradition. The mass wedding is marrying several male and female students in one event. This qualitative research will analyze the traditions that are still alive, especially mass weddings at the Darul Falah Central Islamic Boarding School based on the analysis of Maslahah Mursalah Imam As-Syathiby, whether the tradition embodies a benefit. So that the tradition must be implemented or is only good to be implemented because there is no harm. The results of this study indicate that Maslahah Mursalah is based on the thoughts of Imam As-Syathiby who categorizes that it is divided into three characteristics in implementing its role, namely; Ad-Dharuriyah, Al-Hajjiyah, At-Tahsiniyah. The study in this research concludes that the tradition of mass weddings of male and female students at the Darul Falah Central Islamic Boarding School contains Maslahah of At-Tahsiniyyah nature, although a maslahah in this tradition is not included in the needs of Maslahah that are of a basic nature such as Ad-Dharuriyah and Al-Hajjiyah. At-Tahsiniyah is also important in aspects of community life with the aim of perfecting Islamic religious values. Thus, the study in this research provides an important contribution to a living tradition in order to realize a maslahah that is still valuable in the view of sharia and not merely realizing a maslahah of an individual nature.